2015
DOI: 10.1080/13662716.2015.1105127
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration for Innovation: A Case Study on How Social Capital Mitigates Collaborative Challenges in University–Industry Research Alliances

Abstract: Universities and public research organizations (PROs) are valuable sources of knowledge on innovation development for firms. Differences in goals and approaches between firms and PROs often create tension and lead to challenges that prevent achieving fruitful collaboration. This paper explores how the development of cognitive and relational social capital can mitigate such challenges and encourage fruitful collaboration between firms and PROs in research alliances over time and further lead to the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 62 publications
1
41
0
2
Order By: Relevance
“…Activities can be regarded as investments in network capital which may pay off later (Huggins, Johnston, and Thompson 2012). As soon as firms are convinced that being active in a cluster can be beneficial in the long term, they will start to network and build social capital on the basis of common understandings and common goals (Steinmo 2015). Networking competence incentivises them to connect other cluster firms whenever potential of the cooperative creation is seen as being of additional value.…”
Section: Networking Competencementioning
confidence: 99%
“…Activities can be regarded as investments in network capital which may pay off later (Huggins, Johnston, and Thompson 2012). As soon as firms are convinced that being active in a cluster can be beneficial in the long term, they will start to network and build social capital on the basis of common understandings and common goals (Steinmo 2015). Networking competence incentivises them to connect other cluster firms whenever potential of the cooperative creation is seen as being of additional value.…”
Section: Networking Competencementioning
confidence: 99%
“…Many studies have found a positive relationship between university-industry collaboration and scientific productivity (Ranga et al 2003;Van Looy et al 2011;Rivera-Huerta et al 2011;Banal-Estañol et al 2013;Van Looy et al 2004;Abramo et al 2009;Lee & Bozeman 2005;Landry et al 1996;Tartari & Breschi 2012;Steinmo 2015). Some studies have noted that positive effects only occur under specific conditions (Bonaccorsi et al 2006;Manjarrés-Henríquez et al 2009;Banal-Estañol et al 2013), whereas others have found that collaboration can have negative effects on scientific productivity (Bonaccorsi & Piccaluga 1994;Hottenrott & Thorwarth 2011;Blumenthal et al 1996;Manjarrés-Henríquez et al 2009;Banal-Estañol et al 2015).…”
Section: University-industry Collaboration and Scientific Productivitmentioning
confidence: 99%
“…Prior research has not examined who initiates university-industry collaboration, and specifically to whom the establishment of joint research projects, contract research, inlicensing, consulting, or informal contacts may be attributed. There are not only qualitative differences among the different modes of collaboration but also differences regarding the intrinsic motivations and reward structures between academia and industry (Goel and Rich, 2005;Steinmo, 2015). For instance, joint research projects involve the sharing of research knowledge and potentially withholding or even banning the publication of research results by academics (Czarnitzki, Grimpe, and Toole, 2015b), while contract research involves only the sharing of pertinent research information.…”
Section: Introductionmentioning
confidence: 99%